O Making of de uma grande política pública: Estratégia, planejamento e apoio à decis\~ao na construç\~ao do Plano Marshall - Antônio Lassance (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
This working paper discusses how decision support can contribute to the formulation of public policies to achieve greater consistency and coherence. If decision support fulfills its role, it is assumed that this favors the design of more efficient and effective government programs. In order to investigate these issues in detail, the analysis reconstructs the making of the Marshall Plan, which is considered the greatest and most complex plan ever developed since the twentieth century. Combining in-depth case study methodology, microhistory, and implementation science, the analysis concludes that the presence or absence of strategic formulation, decision support, and implementation planning is part of the "big bang" of policies and programs and determines their trajectories. The conclusions suggest that the reinforcement of the strategic role of decision support advisory staff have practical and concrete effects in defining the theory of change and the scope of intervention, and not the details of the operationalization of specific solutions. The study presents the open method of coordination, used by the New Deal and reproduced in the European Recovery Program, and recommends its use as a policy-making practice targeting greater strategic robustness and programs with proper managerial autonomy. The analysis confronts the crucial issue of the influence of interest groups in policy making. This is something inherent to the democratic process and to the role of the State as a broker. The challenge is to be better equipped to face the risk of capture by predatory interests. This major problem remains badly solved by the more traditional literature on public policy that has served as the bedside book for most policymakers. At the end, we show some documents that remained secret for fifty years. They expose the backstage decision support for the formulation of the Marshall Plan and exemplify, in practice, the strategic role that top-level advisors can play.
Keywords: H11; D04; B15; 330; Marshall Plan; policy design; ex ante analysis of public policies; economic history; political economy